Slot allocation and use at hub airports, perspectives for secondary trading - Wit, Jaap de; Burghouwt, Guillaume (European Journal of Transport and Infrastructure Research, 2008)
The growing excess demand for airport capacity makes an efficient use of capacity at congested airports in Europe in increasingly urgent issue. The key question addressed here focuses on the perspectives for a more efficient use of existing airport capacity through various market based options, especially with regard to hub airports in Europe. To that end the following steps are taken. First, the existing allocation system for scarce airport capacity is described and the inefficiencies in the system are identified. More efficient market based approaches are introduced, ranging from congestion pricing to primary slot auctioning and secondary slot trading. The exemption of the ‘grey’ slot trading market in London is explained. Thereafter, we describe the controversy between the two objectives of slot allocation, i.e. efficient use of slots in the upstream market and sufficient competition in the downstream air transport markets. The substantially different approaches chosen by the US and the EU with respect to preferred market based slot allocation options is analysed in this context of conflicting objectives. We also take account of the Commission’s decision to tolerate slot trading at coordinated airports in Europe. Finally, we discuss the impact of secondary slot trading at hub airports in Europe. We confront the slot trading approach with the hubbing system operated at major congested airports in Europe. Since hubbing results in a daily sequence of peak and off-peak periods, the use of hub airport capacity is inefficient, especially during periods of idle capacity. Finally, we address whether slot trading will improve an efficient use of hub airport capacity and if so, how will the hubbing system adapt to these new conditions. We will use Amsterdam Airport as an example.